Multiple right ventricular thrombi formation following acute myocardial infarction: a case report - U.I. Hewarathna; H.G.W.A.P.L. Bandara; R.M.S.P. Karunarathne; T. Kogulan; N.W. Kodithuwakku; R. Thennakoon; S.R. Jayawickreme; S.N.B. Dolapihilla; G. Mayurathan; D.T. Ambagaspitiya (Sri Lanka Journal of Medicine, 2016)
A 64 year old gentleman presented with features of acute coronary syndrome. Urgent electrocardiogram showed evidence of acute infero-posterior and right ventricular ST segment elevated MI (STEMI). Trans-thoracic echocardiogram (TTE) on admission revealed marked RV and inferior wall hypokinesia with poor RV function. TTE on day three revealed multiple thrombi attached to the RV wall near the ventricular apex. Echocardiogram on the following day revealed coalesced thrombi forming a large mass. This case report illustrates the occurrence of multiple RV thrombi following an episode of acute infero-posterior and right ventricular STEMI. Timely performed TTE can be utilized as a safe, non-invasive and cost-effective diagnostic modality as well as a monitoring tool of the therapeutic outcome of such patients.